Study upon the efficacy of apramycin in the treatment of colibacillosis in young calves - ΣΤΟΦΟΡΟΣ, E.; ΚΥΡΙΑΚΗΣ, Σ.; ΔΟΝΟΣ, Α.; ΠΑΠΑΧΑΡΙΣΗΣ, Γ.; ΑΝΔΡΕΩΤΗ, Γ.; ΤΣΑΛΤΑΣ, Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Apramycin, a new aminocy clitol antibiotic produced by a strain o f S t r e p t o m y c e s te n e b r a r i u s has been evaluated as a treatment of naturally occuring colibacillosis in young calves. Results are reported from 3 field trials, involving 95 animals, in Greece. In 2 of those trials, apramycin was administered orally at a dose rate of 20 and 40 mg/kg bodyweight and at 20 mg/kg b.w. by injection in the 3rd trial (Table I).